Maître-élèves : le risque d'un rapport manqué ? Exploration des conditions d'une école hospitalière - Frédérique-Marie Prot (Recherches en Éducation)
This contribution does not set out an empirical analysis in a contextualized survey, but proposes a theoretical exploration of the conditions for thinking about what the notion of a « hospitable » school might mean. To this end, we are interested in the complexity of the teacher-student relationship from the perspective of building mutual understanding, in the context of a school intrigue that takes place over a long period of time. While the aim is to address ethical questions that lead to an approach to the psychic dimension at work in the relationship, we also invite you to reflect on the inclusion of this dimension in the didactic aspects inherent in the practice of transmitting culture. First, we'll look at the conditions under which the idea of a hospital school does not contradict itself or fall within the logic of illusion. Secondly, we'll look more specifically at the relationship between teacher and pupil, and with it the necessary interweaving of the psychic and the didactic. At the end of this journey, we hope that the possibility of real school hospitality will seem more established.